Altered Dynamic Amplitude of Low-Frequency Fluctuations in Patients With Migraine Without Aura - Chen, Hong; Qi, Guiqiang; Zhang, Yingxia; Huang, Ying; Zhang, Shaojin; Yang, Dongjun; He, Junwei; Mu, Lan; Zhou, Lin; Zeng, Min (Frontiers in Human Neuroscience, 2021)
Migraine is a chronic and idiopathic disorder leading to cognitive and affective problems. However, the neural basis of migraine without aura is still unclear. In this study, dynamic amplitude of low frequency fluctuations (dALFF) analyses were performed in 21 patients with migraine without aura and 21 gender and age matched healthy controls to identify the voxel-level abnormal functional dynamics. Significantly decreased dALFF in bilateral anterior insula, bilateral lateral orbitofrontal cortex, bilateral medial prefrontal cortex, bilateral anterior cingulate cortex, and left middle frontal cortex were found in patients with migraine without aura. The dALFF values in anterior cingulate cortex were negatively correlated with pain intensity, i.e. visual analog scale. Finally, support vector machine was used to classify patients with migraine without aura from healthy controls achieved an accuracy of 83.33%, sensitivity of 90.48%, and specificity of 76.19%. Our findings provide the evidence that migraine influences the brain functional activity dynamics and reveal neural basis for migraine, which could facilitate understanding the neuropathology of migraine and future treatment.